2005
DOI: 10.1016/s0377-1237(05)80009-7
|View full text |Cite
|
Sign up to set email alerts
|

Phacotrabeculectomy Versus Conventional Combined Technique in Coexisting Glaucoma and Cataract

Abstract: Phacotrabeculectomy provides effective and sustained visual recovery and adequate control of intraocular pressure as compare to conventional combined procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…10 Similarly perasalo etall in study of 243 cases of phacotreb reported 80% cases with visual improvement and 70% cases IOP control without drugs. 11 Our study confirms the safety and effectiveness of combined single site phacoemulsification with IOL implantation and trabeculectomy.…”
Section: Discussionmentioning
confidence: 91%
“…10 Similarly perasalo etall in study of 243 cases of phacotreb reported 80% cases with visual improvement and 70% cases IOP control without drugs. 11 Our study confirms the safety and effectiveness of combined single site phacoemulsification with IOL implantation and trabeculectomy.…”
Section: Discussionmentioning
confidence: 91%
“…This leads to the question—does modern cataract surgery allow a less hazardous profile of phacotrabeculectomy? The answer remains unclear and there is a lack of consensus on the best surgical management for these patients [ 19 – 22 ].…”
Section: Introductionmentioning
confidence: 99%